Analisis Cover Buku Teks Sejarah di SMA Kurikulum Merdeka - Widyawati, Diah; Nindiati, Dina Sri; Syafarudin, Nur (PPSDP Undergraduate Journal of Educational Sciences, 2025)
History textbooks are a learning resource used by students at school to convey material, many history textbooks can be used as companions when one textbook does not contain the necessary material. The purpose of this study is what are the social studies learning resources textbooks for high school history independent curriculum. This research method is a literature study, with data analysis in the form of content analysis focused on high school history textbooks at school. The results state the learning resources of history textbooks for the independent learning curriculum in high school include history textbooks for class X of vocational schools, social studies textbooks for history class X of high school, social studies textbooks for class X history of high school by Erlangga, history textbooks for class XI of high school, history textbooks for class XI by Erlangga and history textbooks for class XII of high school. It can be concluded that the findings of the history textbook sources have the content of the history material edition of the independent learning curriculum. The sources of history textbooks of the independent curriculum can be used as a reference to improve critical thinking and historical values for students as future generations.